Adopsi Teknologi Pembayaran Digital QRIS di Kalangan UMKM Labuan Bajo: Tantangan dan Peluang - Petrus Suhardi Ekaputra; Fitri Ciptosari; Tedy Halim (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
This study aims to analyze the challenges and opportunities in adopting the QRIS digital payment technology among MSMEs in Labuan Bajo, Indonesia. In the context of tourism development and transaction digitalization, QRIS is considered to enhance operational efficiency and customer accessibility for business owners. However, the adoption of this technology still faces several barriers, such as low technology literacy, limited digital infrastructure, and concerns over transaction security. A qualitative research method was employed, involving in-depth interviews with 15 MSME operators. The findings reveal that the ease of use and relative advantages of QRIS encourage adoption by some MSMEs, especially those serving tourists. However, internet access limitations and low technological understanding significantly hinder its broader implementation. The study recommends improving digital literacy and upgrading infrastructure to accelerate QRIS adoption in the tourism sector.